Graphene-enabled metasurface with independent amplitude and frequency controls in orthogonal polarization channels. (25th March 2023) - Li, Qingge; Zhang, Jin; Rukhlenko, Ivan D.; Zhu, Weiren
Abstract: Graphene-based metasurfaces offer a novel approach to the dynamic manipulation of electromagnetic waves. Until now most of active graphene-based metasurfaces operating with microwaves have been able to control only one wave parameter, e.g, amplitude or frequency, while the realization of independent dual parameter control is rare and remains challenging. Here we report on the design, modelling, fabrication, and characterization of a graphene-based absorbing metasurface capable of independent dynamic control of reflection amplitude in one polarization channel and resonance frequency in another. Numerical simulations show that varying the resistance of the graphene sheet in the designed metasurface allows one to change the amplitude of the reflected x -polarized wave by more than 13 dB and shift the resonance frequency of the absorption spectrum of the y -polarized wave from 3.35 to 4.60 GHz. The dual tunability feature is analysed using the transmission line theory and the lumped-element model of the metasurface and experimentally demonstrated via the fabrication and testing of the metasurface. This work brings a new degree of freedom to tunable graphene-based metasurfaces for controlling microwaves with potential applications in communications, wireless transmission, and sensing. Graphical abstract: Highlights: Experimentally proposing a graphene-based absorbing metasurface with independent amplitude and frequency regulations. Introducing dual polarization to achieve different tunable functions for different polarizations. Electrically regulating chemical potential of the sandwich graphene strip to achieve dual tunability.